148k views
7 votes
Question is attached​

Question is attached​-example-1

1 Answer

7 votes

Answer:

Please check explanations

Explanation:

Mathematically;

csc 2 theta = 1 / sin 2 theta

Sin 2 theta = sin (theta + theta)

= 2sin theta cos theta

So therefore;

csc 2 theta = 1/2(sin theta cos theta)

= 1/2 * 1/sin theta * 1/ cos theta

1/sin theta = csc theta

1/cos theta = sec theta

Thus;

csc 2 theta = 1/2 * csc theta * sec theta

csc 2 theta = 1/2 sec theta csc theta

User Andrea Gorrieri
by
4.7k points